Interplay between dental pulp tissue osteoprotegerin and TNF-α levels with micromorphological changes in the teeth of patients with chronic pulpitis - Šubarić, Ljiljana B.; Šubarić, Aleksandar S.; Djordjević, Nadica S.; Filimonović, Jelena S.; Jovanović, Radovan R.; Perić, Dejan; Inić, Sofija G.; Inić, Ružica G.; Stojanović, Zdenka; Đorđević, Aleksandar M. (Vojnosanitetski pregled, 2024)
Background/Aim. Chronic pulpitis (CP) is an inflammatory dental pulp disorder associated with various pathophysiological mechanisms in its origin. The aim of the study was to evaluate the changes in the pulp tissue of osteoprotegerin (OPG) and tumor necrosis factor (TNF)-α and establish their relationship with the histological changes of pulp tissue, as well as with the micromorphological changes, occurring in the mineralized tissue. Methods. The study examined the dental pulp of 41 patients with CP and 12 healthy individuals. The group of the diseased subjects was subdivided based on the presence of communication of the pulp with the oral cavity, i.e., open (n = 22) or closed (clausa) (n = 19) CP. Results. The levels of TNF-α were statistically significantly increased, while OPG levels were decreased in the pulp of patients with CP, compared to the control group. TNF-α levels were almost the same in the pulp of patients with closed CP and the control group, while values were significantly increased in those with open CP compared to control. Histopathological analysis showed a significant increase in the number of mononuclear inflammatory cells in the diseased pulp. Scanning electron microscopy showed distinct changes, which correlate with internal resorption. Conclusion. The results indicate a much greater and intensified process of root resorption in patients with closed CP, which is unassociated with dental pulp OPG and TNF-α level changes.
Keywords: cytokines; dental pulp; histological techniques; microscopy, electron, scanning; osteoprotegerin; tumor necrosis factor-alpha